Nitrogen-Induced Soil Acidification Reduces Soil Carbon Persistence by Shifting Microbial Keystone Taxa and Increasing Calcium Leaching - Ding Wang; Jie Wang; Yuting Zhang; Xinping Chen; Ji Chen; Xiaojun Shi (Agronomy, 2025)
Anthropogenic nitrogen (N) enrichment alters soil biotic (e.g., microbial metabolism) and abiotic (e.g., pH and mineralogy) properties, substantially affecting the persistence and storage of soil organic carbon (SOC). However, the response of relatively persistent mineral-associated organic carbon (MAOC) to N enrichment and the underlying mechanisms are not well understood, leading to significant uncertainties regarding SOC stability under continuous N input. Based on a 15-year field N fertilisation experiment (0, 28.5, 60.0, 72.0 g N m−2 yr−1), we studied the responses of MAOC to N input and the associated changes in soil mineralogy and microbiology. N fertilisation significantly reduced MAOC content by 16.0%. The loss of MAOC was primarily attributed to soil acidification (pH decreased from 6.4 to 4.2), leading to exchangeable calcium (Ca) leaching and loss of Ca-bound organic carbon by 37.9% on average. Furthermore, N-induced shifts in dominant microbial keystone taxa from K-strategists (e.g., Actinobacteriota and Sordariomycetes) to r-strategists (e.g., Subgroups 4 and 6 Acidobacteriota) impeded the formation of MAOC through the reduction of microbial carbon use efficiency and oxidase activity (e.g., phenol oxidases and peroxidases). These results suggest that keystone taxa play crucial roles in regulating carbon metabolism and are responsible for MAOC reduction. Moreover, our data pinpoint the importance of Ca leaching for SOC destabilisation, particularly in near-neutral and neutral soils.